Education Hybridization of Pesantren and its Challenges in Rural Industrialization - Hadi, Syamsul; Soetarto, Endriatmo; Sunito, Satyawan; Pandjaitan, Nurmala K. (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2016)
This research aims to explain the existence, institutional environment and the sustainability of pesantren institutions in the village that experienced urbanization because of industrialization and the culture of modernity. The study used a constructivism paradigm for qualitative method. Data mining is done through in-depth interview techniques and field observations with the support of document studies. The results showed that, in responding to the instrumentation (the interests) of the state and the pragmatic market demands Pesantren Manbail Futuh pursuing a strategy of hybridization and the commodification of education. It is to adopt a policy of state education as well as to accommodate the community's preference based on the general education schools that is based in Pesantren. Hybridization of education is a diversification of education units (religious and general) in Pesantren. While commodification is intended as fundraising efforts to support the operational needs of the institution so that the implementation of formal education units shall meet national education standards (NES) in addition to meeting society's expectations (market). This strategy means a form of guarantee for the existence and sustainability of pesantren institutions in rural communities.